Extra-skeletal Ewing's sarcoma, a rare condition of the submandibular salivary gland, a case report - Abdul-Aziz Alaqeeli (21323699) (2022)
Extra-skeletal Ewing's sarcoma (ESS) is rarely found in the head and neck region, soft tissue presentation of Ewing's sarcoma is uncommon, morphologically it resembles Ewing's sarcoma originates from bone. We report a case of extra-skeletal Ewing's sarcoma of the submandibular gland region in a 34-year-old male including clinical, radiological, histopathological presentation and, treatment plan. To the best of our knowledge, it has been once only reported to arise from the submandibular gland. Other Information Published in: Oral and Maxillofacial Surgery Cases License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.omsc.2022.100252